Pelatihan Pembuatan Lilin Aromateraphy Dari Limbah Minyak Jelantah di Desa Jabung - Alawia, Mutia Tsalitsa; Farida, Wiwik Mukholafatul (JPM (Jurnal Pemberdayaan Masyarakat), 2025)
The participants of this training are members of the Family Welfare Empowerment (PKK) group and Micro, Small, and Medium Enterprise (UMKM) entrepreneurs in Jabung Village, Talun, Blitar. The issue faced by the people of Jabung is the waste cooking oil produced from household leftovers and UMKM production. This community service aims to provide training to the community on how to utilize waste cooking oil to make aromatherapy candles, as an effort to reduce waste cooking oil produced from household and UMKM waste by enhancing the creativity of the PKK members and UMKM entrepreneurs. The community service is carried out using the Asset-Based Community Development (ABCD) method by leveraging the potential owned by the community. The stages of the training consist of observation and analysis of community needs, activity preparation, training implementation, and activity evaluation. As a result of this community service, the participants are enthusiastic and have successfully learned how to process waste cooking oil into aromatherapy candles with high utility and market value, which can also become a business idea and a potential opportunity to help improve household economies.